Tertiary lymphoid structures in renal cell carcinoma: from heterogeneity dissection to translational precision immunotherapy - Li, Zhexian; Ruan, Sensen; Yu, Yang; Xiang, Hao; Mi, Wenjie (Frontiers in Immunology, 2026)
Renal cell carcinoma (RCC), characterized by its distinctive hypoxic and immunosuppressive tumor microenvironment (TME), demonstrates suboptimal responses to current immunotherapeutic interventions. Tertiary lymphoid structures (TLS), defined as ectopically organized immune cell aggregates that develop in non-lymphoid tissues, function as “plastic immune organs” and exhibit considerable promise as both prognostic indicators and therapeutic targets. Notably, TLS in RCC manifest significant heterogeneity, with specific subsets associated with favorable clinical outcomes while others correlate with adverse prognosis. This review systematically examines the cellular composition, formation, classification criteria, and evaluation methods of TLS in RCC, with particular emphasis on the relationship between TLS heterogeneity and differential prognostic implications. We further explore potential regulatory mechanisms underlying these divergent clinical outcomes and provide a comprehensive synthesis of current TLS-targeted therapeutic strategies, including recent clinical advancements. Finally, we delineate the prevailing challenges in TLS research and propose future directions. This work provides a theoretical foundation and research framework for future patient outcome-oriented prospective studies and clinical trials, while also offering insights for the development of TLS-related precision immunotherapy strategies.